1984
DOI: 10.1080/0141192840100206
|View full text |Cite
|
Sign up to set email alerts
|

Factors in the Use of Lap‐dissolve Presentation Methods for Teaching the Visualisation of Spatial Transformations

Abstract: Two experiments were performed to study the effects of varying the exposure-time and the dissolve-time in the use of a lap-dissolve control unit in presenting programmes intended to teach 14-15-year-old students to visualise the effects of performing reflections and rotations on molecules represented in diagrams. Both experiments employed a two-dimensional design with three levels for each of the two factors. The Rotations Programme was not effective with any of the combinations of exposure-and dissolve-times.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

1985
1985
1986
1986

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
0
5
1
Order By: Relevance
“…However, there was a significant difference between the mean of the control and that of the experimental group that had not used the models (p<0-05). The results of the present experiment differ from those of Seddon El Farra and Jusoh (1984) in that the programmes based only on diagrams brought about significant learning with students of this age group. It seems probable that the different results arise because the speeds of rotation were different in the two experiments.…”
Section: Resultscontrasting
confidence: 83%
See 3 more Smart Citations
“…However, there was a significant difference between the mean of the control and that of the experimental group that had not used the models (p<0-05). The results of the present experiment differ from those of Seddon El Farra and Jusoh (1984) in that the programmes based only on diagrams brought about significant learning with students of this age group. It seems probable that the different results arise because the speeds of rotation were different in the two experiments.…”
Section: Resultscontrasting
confidence: 83%
“…While the technique based upon the models has been found to be effective with a variety of age groups (Seddon, Eniaiyeju andJusoh 1984, Jusoh 1979), it has also been found that the sequential presentation of the diagrams was not at all effective in teaching the visualization of rotations to 15-year old English students (Seddon, El Farra and Jusoh 1984). Perhaps the demands of understanding the diagrammatic sequences were too abstract for students at this level of cognitive development, whereas the models provided a more appropriate concrete form of representation.…”
Section: Rotation Aboutmentioning
confidence: 95%
See 2 more Smart Citations
“…The teaching method of Seddon & Shubber was based on that developed and used extensively by Seddon and various co-workers (e.g. Seddon, Eniaiyeju & Jusoh, 1984;Seddon, Tariq & Dos Santos Veiga, 1984;Seddon, El Farra & Jusoh, 1984), and uses instructional programmes in which students observe sequences of diagrams each representing a three-dimensional structure at successive stages during a rotation. Seddon & Shubber hypothesised that using colour in the drawing of different parts of the diagrams would enable students to compare more easily the position of corresponding parts of a structure in successive diagrams, and thereby help students to see what should happen to the different parts of the diagrams as the structure rotates.…”
mentioning
confidence: 99%